The Level of Serum Enzymes and Hormones in Patients with Miscarriage - Shreewastav, Rupesh Kumar; Yadav, Munzal (Journal of Nepal Health Research Council, 2025)
Background:The level of various enzymes and thyroid hormones in blood get altered during miscarriage, which can have predictive value or importance as a biomarker for the diagnosis. The aim of the present study is to validate the alteration in the level of serum enzymes and thyroid hormones in patients suffering with miscarriage in a tertiary care hospital in Nepal. Methods: A descriptive cross-sectional study was carried out on patients suffering with miscarriage and admitted for treatment in Nobel Medical College Teaching Hospital. Demographic data were recorded in a predesigned performa. The level of various enzymes and thyroid hormones were estimated from the blood sample of patients in the department of biochemistry laboratory. Data were entered in MS excel and analyzed by statistical package for the social sciences Version version 20.0 Results: The total number of patients suffering from miscarriage and enrolled in the study was 86. The mean value of serum gamma glutamyl transferase, lactate dehydrogenase and adenosine deaminase in these patients were 22.67±8.22, 289.6±126.9 and 21.3±9.9 IU/ml respectively, which were significantly higher (p=<0.0001, 0.0004, 0.0179 respectively) when compared to healthy pregnant women. Thyroid dysfunction was noted in 15 (17.44%) patients, out of that Subclinical hypothyroidism was most common and affected 8(9.3%) individuals. Conclusions:The mean value of serum gamma glutamyl transferase, lactate dehydrogenase and adenosine deaminase in case of miscarriage was found to be elevated significantly and thyroid dysfunction was also noted to small fraction of patients suffering from miscarriage with Subclinical hypothyroidism being the most common. Keywords: Enzyme; hormone; miscarriage.